2015
DOI: 10.1016/j.outlook.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Implementing common data elements across studies to advance research

Abstract: Challenges arise in building the knowledge needed for evidence based practice partially because obtaining clinical research data is expensive and complicated, and many studies have small sample sizes. Combining data from several studies may have the advantage of increasing the impact of the findings, or expanding the population to which findings may be generalized. The use of common data elements will allow this combining and, in turn, create big data, which is an important approach that may accelerate knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…However, these six included studies have used different types of cognitive‐behavioural interventions and different assessment instruments to measure effectiveness, which make the identification of best practices challenging. Therefore, in the future, using common assessment tools to measure occupational stress across studies would allow for a combination of data from multiple investigations, which can potentially increase the impact of the findings or expand the population to which the findings can be generalized …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these six included studies have used different types of cognitive‐behavioural interventions and different assessment instruments to measure effectiveness, which make the identification of best practices challenging. Therefore, in the future, using common assessment tools to measure occupational stress across studies would allow for a combination of data from multiple investigations, which can potentially increase the impact of the findings or expand the population to which the findings can be generalized …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the future, using common assessment tools to measure occupational stress across studies would allow for a combination of data from multiple investigations, which can potentially increase the impact of the findings or expand the population to which the findings can be generalized. 29 In terms of MBI, this review included three studies that evaluated MBI with regard to managing occupational stress among nurses working in ICUs. 10,23,25 The consensus across these three studies was that the MBI is effective in reducing stress among critical care nurses These findings were consistent with an updated systematic review which found that MBSR and MBCT are effective in reducing occupational stress, depression, and anxiety affecting the mental health of employees.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, by incorporating CDEs into research protocols, and depositing data generated in an accessible, common data repository, nursing researchers and others will have the opportunity to address more complex questions and advance the field in a way not possible when individuals work alone or in silos (Cohen, Thompson, Yates, Zimmerman, & Pullen, 2015; Corwin et al, 2014). …”
Section: Common Data Elementmentioning
confidence: 99%
“…Objectives of the CDE project include: (1) to identify common data elements used in clinical research; (2) to present data elements in standard, widely available formats; (3) to establish common definitions and validate permissible values and ranges to guide researchers in selecting CDEs most applicable to studies; (4) to standardize case report forms and other instruments; and (5) to provide standardized information to researchers for database development. Common data elements can accelerate the pace of clinical research for rare diseases by rendering data more comparable and facilitating multi-center and international efforts [12]. …”
Section: Approaches For Assessing Cognition and Behaviormentioning
confidence: 99%